Glycated hemoglobin concentrations of red blood cells minimally increase during storage under standard blood banking conditions. Issue 2 (1st October 2018) - Prosenz, Julian; Öhlinger, Thomas; Müllner, Ernst W.; Marculescu, Rodrig; Gerner, Christopher; Salzer, Ulrich; Kiefer, Florian W.; Baron, David M.
Abstract : BACKGROUND: Few and inconsistent data exist describing the effect of storage duration on glycated hemoglobin (HbA1c) concentrations of red blood cells (RBCs), impeding interpretation of HbA1c values in transfused diabetic patients. Hence the aim of this study was to evaluate to what extent HbA1c concentrations of RBCs change during the maximum allowed storage period of 42 days. STUDY DESIGN AND METHODS: Blood was drawn from 16 volunteers, leukofiltered, and stored under standard blood banking conditions. HbA1c concentrations of RBCs were measured on Days 1 and 42 of storage using three different validated devices (ion‐exchange high‐performance liquid chromatography Method A1 and A2, turbidimetric immunoassay Method B). RESULTS: Mean HbA1c concentrations of RBCs on Day 1 were 5.3 ± 0.3% (Method A1), 5.4 ± 0.4% (Method A2), and 5.1 ± 0.4% (Method B). HbA1c concentrations increased to 5.6 ± 0.3% (A1, p < 0.0001), 5.7 ± 0.3% (A2, p = 0.004), and 5.5 ± 0.4% (B, p < 0.0001) on Day 42, respectively, corresponding to a 1.06‐fold increase across all methods. Glucose concentrations in the storage solution of RBCs decreased from 495 ± 27 to 225 ± 55 mg/dL (p < 0.0001), confirming that stored RBCs were metabolically active. CONCLUSION: These results suggest a significant, albeit minor, and most likely clinically insignificant increase in HbA1c concentrations during storage of RBCs for 42 days.